1983
DOI: 10.1152/ajpheart.1983.244.2.h201
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and renal response to plasma volume expansion in the primate Macaca mulatta

Abstract: The purpose of this study was to investigate the hormonal and renal response to plasma volume expansion in the ketamine-anesthetized rhesus monkey. The blood volume was determined in nine animals and found to be 6% of the body weight. Six monkeys received isoncotic isotonic fluid amounting to 25% of the blood volume. Plasma volume expansion led to significant decrease in the plasma concentrations of antidiuretic hormone (46.7%) and aldosterone (78.4%) as well as plasma renin activity (50.0%). The mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the monkey, Gilmore et al (1980) found that ADH fails to change when blood volume is expanded 30% whereas Billman et al (1983) have recently reported that ADH and renin decrease with a 25% blood volume expansion. Experiments in humans using head-out water immersion, a hypervolemic stimulus in which blood is translocated to expand the cardiopulmonary blood volume and elicits a marked diuresis, have also been inconclusive in that both decreases (Epstein et al, 1980) and increases (Kravik et al, 1982) in ADH levels have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the monkey, Gilmore et al (1980) found that ADH fails to change when blood volume is expanded 30% whereas Billman et al (1983) have recently reported that ADH and renin decrease with a 25% blood volume expansion. Experiments in humans using head-out water immersion, a hypervolemic stimulus in which blood is translocated to expand the cardiopulmonary blood volume and elicits a marked diuresis, have also been inconclusive in that both decreases (Epstein et al, 1980) and increases (Kravik et al, 1982) in ADH levels have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…After 3-4 periods of relatively constant urine flow, each animal was volumeexpanded 20% of estimated blood volume with 6% high molecular weight dextran in isotonic saline (6% Gentran 75, Travenol), the volume being infused by hand over a 5-to 6-minute period. Blood volume was estimated as 6% of body weight (Billman et al, 1983). The experiment was continued until urine flow declined to a value at least onehalf of its peak diuresis value, or no sooner than 120 minutes post expansion.…”
Section: Methodsmentioning
confidence: 99%
“…Stretch receptors having effects on renal function have been found in the renal (17) and hepatic vasculature (13,25) so these remain a viable possibility in our denervated animals unless their effects are dependent on intact vagal input to the central nervous system. With regard to possible humoral substances involved, Billman et al (1) have reported that ADH, renin and aldosterone levels decrease with volume expansion in the intact monkey but it is not known how important these humoral effects are in mediating the renal excretory responses or if these hormone levels could decrease in our denervated animals. Also, as discussed earlier, ADH levels do not need to decrease in order for CH2O to increase in the monkey (31).…”
Section: / L___~j'! ; Y--4___ ---L Tmentioning
confidence: 85%
“…Extrarenal factors such as excess extracellular fluid volume have been known to modify fluid reabsorption independent of changes in GFR and thus increase tubule fluid flow rate (37). Plasma volume expansion by infusion of either physiologic saline solution (38,39) or a colloid solution (40) has been reported to result in an overall increase in salt and water excretion and a decrease in plasma antidiuretic hormone (ADH), renin, and aldosterone. Though the cause of the increases in urine output rate, FES, and CHIO in the present study cannot be determined from our data, it is most likely that the changes are ascribed to a plasma volume expansion that was caused by infusion of the PHP solution.…”
Section: Discussionmentioning
confidence: 99%